Early Experiences in the Integration of Non-communicable Diseases into Emergency Primary Health Care, Beni Region, Democratic Republic of the Congo. Issue 1 (19th March 2021) - Ratnayake, Ruwan; Wittcoff, Alison; Majaribu, John; Nzweve, Jean-Pierre; Katembo, Lambert; Kasonia, Kambale; Nzanzu, Adelard Kalima; Kiapi, Lilian; Ngoy, Pascal
Background: Health services in humanitarian crises increasingly integrate the management of non-communicable diseases into primary care. As there is little description of such programs, this case study aims to describe the initial implementation of non-communicable disease management within emergency primary care in the conflict-affected Beni Region of Democratic Republic of the Congo (DRC). Objectives: We implemented and evaluated a primary care approach to hypertension and diabetes management to assess the feasibility of patient monitoring, early clinical and programmatic outcomes, and costs, after seven months of care. Methods: We designed clinical and programmatic modules for diabetes and hypertension management for clinical officers and the use of patient cards and community health workers to improve adherence. We used cohort analysis (April to October 2018), time-trend analysis, semi-structured interviews, and costing to evaluate the program. Findings: Increases in consultations for hypertension (incidence rate ratio [IRR] 13.5, 95% CI 5.8–31.5, p < 0.00) and diabetes (IRR 3.6, 95% CI 1–12.9, p < 0.05) were demonstrated up to the onset of violence and an Ebola epidemic in August 2018. Of 833 patients, 67% were women of median age 56. Nearly all were hypertensives (88.7%) and newly diagnosed (95.9%). Treatment adherence, defined as attending ≥2 visits in the seven month period, was demonstrated by 45.4% of hypertension patients. Community health workers had contact with 3.2–3.8 patients per month. Respondents stated that diabetes care remained fragmented with insulin and laboratory testing located outside of primary care. Program and management costs were 115 USD per person per treatment course. Conclusions: In an active conflict setting, we demonstrated that non-communicable disease care can be well-organized through clinical training and cohort analysis, and adherence can be addressed using patient-held cards and monitoring by community health workers. Nearly all diagnoses were new, emphasizing the need to establish self-management. Insecurity reduced access for patients but care continued for a subset of patients during the Ebola epidemic.